Bahan cetakan disain kelas yang literat di kelas awal sekolah dasar - Sulaiman Samad; Suardi Suardi (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
The Community Partnership Program (PKM) program is the Pare-Pare City Education Office. The main problem of partners is that making literacy media as a display material in early classes that can attract students' attention as a main prerequisite in designing literacy classes is not easy for elementary school teachers. This factual condition is partly due to the limited reading material that can inspire about media and use to create display material in class. The specific problems that cause this are: (1) limited teacher knowledge about various things that can be developed in the classroom so that students have the expected reading skills; (2) limited teacher skills in making various early grade literacy media that can be used as material to design classes that support the development of student literacy skills; and (3) the low ability of teachers to use various types of media in developing students' literacy skills in early grades. The method used is a participatory training model with the application of ICARE (introduction, connection, application, reflection, and extension). The results obtained are: (1) partners get insights about things that can be developed in the classroom so that students have the expected literacy skills; (2) partners succeeded in creating a variety of early grade literacy media that can be used as material to design classes that support the development of student literacy skills; and (3) partners can use various media in developing students' literacy skills in the early grades.